A Biomechanical Study of Two Distinct Methods of Anterior Cruciate Ligament Rupture, and a Novel Surgical Reconstruction Technique, in a Small Animal Model of Posttraumatic Osteoarthritis - Ramme, Austin J.; Lendhey, Matin S.; Strauss, Eric J.; Kennedy, Oran D. (The Journal of Knee Surgery, 2018)
Small animal models are critical for studies of sports-related knee injury and disease such as posttraumatic osteoarthritis (PTOA) following anterior cruciate ligament (ACL) rupture. In such models, ACL damage can be achieved by surgical transection or, using a more recent innovation, by noninvasive biomechanical means. Whether these approaches differentially alter normal mechanics is unknown. Furthermore, while surgical reconstruction of ruptured ACL can greatly improve joint stability, its effect on PTOA development is also unclear. Our primary purpose was to characterize rodent knee joint mechanics in two models of ACL rupture using a novel quantitative laxity mechanical test. Our secondary aim was to characterize a new reconstruction technique using autograft tail tendon, and to assess its effect on joint mechanics. Our hypothesis was that surgical ACL transection would have a greater effect on joint mechanics. A total of 24 rat knee specimens underwent surgical or biomechanical ACL rupture and were stabilized using a new reconstruction technique using autograft tail tendon. Joint mechanics were assessed three times; preinjury, postinjury, and again after reconstruction, using quantitative joint laxity testing. Primary test readouts were maximum anteroposterior (AP) laxity, loading curve slope, and energy absorption. Student's t-tests were performed to identify intragroup differences. All surgical transections were completed successfully; maximum load in the biomechanical model was 67 ± 7.7 N, with a coefficient of variation of 11.43%. Surgical transection caused increased AP laxity, while biomechanical injury nonsignificantly increased this parameter. In both cases, these changes recovered to baseline by reconstruction. Loading curve slope was reduced in both models and was also returned to baseline by repair. Energy absorption followed the same pattern except it remained significantly different from baseline postreconstruction in the surgical group. This study supports our hypothesis knee joint mechanics is differentially affected by injury mechanism in a small animal model. We also report a novel reconstruction technique in this model, using autograft tail tendon.
Keywords: ACL; laxity; surgical reconstruction; animal model; PTOA